2018
DOI: 10.1142/s1793545818500335
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared laser irradiation of a multilayer agar-gel tissue phantom to induce thermal effect of traditional moxibustion

Abstract: Traditional moxibustion therapy can stimulate heat and blood-vessel expansion and advance blood circulation. In the present study, a novel noncontact-type thermal therapeutic system was developed using a near-infrared laser diode. The device allows direct interaction of infrared laser light with the skin, thereby facilitating a controlled temperature distribution on the skin and the deep tissues below the skin. While using a tissue-mimicking phantom as a substitute for real skin, the most important optical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…There were slight differences in the determined optical properties in comparison to values published for various agar-based phantoms. Cho et al [30] reported an absorption coefficient of 0.24 cm À1 for skin and 0.52 cm À1 for fat tissue while in another study by Iizuka et al [31] values of 0.50 AE 0.04 and 0.7 AE 0.1 cm À1 for unspecified tissue samples was given. This demonstrates the concentrations and different constituents of the fabricated phantoms, which are decisive factors for their optical properties [14,31].…”
Section: Resultsmentioning
confidence: 96%
“…There were slight differences in the determined optical properties in comparison to values published for various agar-based phantoms. Cho et al [30] reported an absorption coefficient of 0.24 cm À1 for skin and 0.52 cm À1 for fat tissue while in another study by Iizuka et al [31] values of 0.50 AE 0.04 and 0.7 AE 0.1 cm À1 for unspecified tissue samples was given. This demonstrates the concentrations and different constituents of the fabricated phantoms, which are decisive factors for their optical properties [14,31].…”
Section: Resultsmentioning
confidence: 96%
“…Agar in different concentrations is widely used for fabricating tissue phantoms [ 46 , 49 ]. For a concentration range of agar from 2.5% to 3.5%, the thermal properties of the agar-based phantom are similar to the thermal properties of many soft tissues [ 46 ]. In this condition, when the temperature reaches around 60 °C to 62 °C, the phase change from solid to liquid occurs.…”
Section: Methodsmentioning
confidence: 99%
“…These phantoms usually require constituent materials whose physical properties accurately represent key tissue characteristics such as the capacity to absorb and transfer the heat [ 45 ]. In particular, agar-based phantoms have been selected thanks to their thermal properties similar to the ones of biological tissue [ 46 , 47 , 48 , 49 , 50 ]. The main advantage of using tissue-mimicking phantoms is that tissue models can be constructed with well-defined physical properties and dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…At first, we used a 3% agar gel phantom mimicking the thermal properties of the biological tissue (Fig. 3(a)) [26]. The homogeneity of the phantom makes it suitable for a preliminary analysis of our data-assimilation Bayesian framework.…”
Section: G Experimental Setupmentioning
confidence: 99%